Menghadirkan Kesejahteraan Berbasis Rumah Tuhan: Penyuluhan Moderasi Beragama bagi Tokoh Lintas Agama Kemenag Bone bolango - Supandi Rahman (Komunal Jurnal Pengabdian Masyarakat, 2022)
In fact, there is no religion on earth that loves poverty. Religions must unite to direct all available resources to combat socio-economic inequality. Because the biggest obstacle to the religious moderation program is poverty and poverty is one of the main routes for acts of extremism. This is where the importance of the implementation of religious moderation counseling for actors of religious harmony in the Office of the Ministry of Religion of Bone Bolango Regency with the theme "presenting welfare based on the house of God". The method applied in this service consists of four stages. The first is consultation with the Ministry of Religion, the second is to prepare extension materials. The three small surveys on several tourist attractions in Bone Bolango to be used as an integrative program of religions and the four stages of implementing outreach to the community in this case the actors of religious harmony (Islam, Catholicism, Protestantism, Hinduism, Buddhism and Confucianism). The counseling materials include discussions about poverty as the enemy of all religions, efforts to bring prosperity based on the house of God and an integrative program of religions, in this case the revitalization of the Ulantha Fort tourist attraction.